2005
DOI: 10.1182/blood-2004-11-4390
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids inhibit activation-induced cell death (AICD) via direct DNA-dependent repression of the CD95 ligand gene by a glucocorticoid receptor dimer

Abstract: Glucocorticoids (GCs IntroductionUpon triggering of their T-cell receptor (TCR), resting naive T lymphocytes are activated to elicit an immune response. In contrast, preactivated T cells undergo activation-induced cell death (AICD) in response to the same signal. [1][2][3] Apoptosis by AICD is an important mechanism to down-regulate the number of reactive T cells and to terminate the immune response. 4 The main apoptotic pathway of AICD is mediated by the CD95 (apoptosis antigen-1 [APO-1]/Fas) death receptor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 71 publications
2
68
1
4
Order By: Relevance
“…This was notable because adult human T cells take 5 to 6 days to reach a plateau of CD95 expression (data not shown). However, murine T cells were also sensitized toward CD95L faster than adult T cells after TCR stimulation, 24 which suggests that naive human cord blood T cells share similarities with murine T cells. Simultaneous FACS analysis of memory cell markers during the in vitro stimulation of cord blood T regs revealed that CD45RO increased more gradually than CD95 ( Figure 5B) and that CD45RA and CD31 were gradually lost until day 6 (data not shown).…”
Section: Tcr-stimulated Cord Blood T Regs Are Sensitive To Cd95l-medimentioning
confidence: 98%
“…This was notable because adult human T cells take 5 to 6 days to reach a plateau of CD95 expression (data not shown). However, murine T cells were also sensitized toward CD95L faster than adult T cells after TCR stimulation, 24 which suggests that naive human cord blood T cells share similarities with murine T cells. Simultaneous FACS analysis of memory cell markers during the in vitro stimulation of cord blood T regs revealed that CD45RO increased more gradually than CD95 ( Figure 5B) and that CD45RA and CD31 were gradually lost until day 6 (data not shown).…”
Section: Tcr-stimulated Cord Blood T Regs Are Sensitive To Cd95l-medimentioning
confidence: 98%
“…Glucocorticoids have been hypothesized to have multiple roles from directing selection processes in T-cell maturation 1 and molding the T-cell repertoire 2 to regulating thymocyte apoptosis following polyclonal T-cell activation. 29 However, the central requirement for de novo gene expression in glucocorticoidmediated apoptosis of thymocytes is clearly established. 4,5 Using DNA microarrays, we identified genes upregulated in primary thymocytes on exposure to the glucocorticoid, dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the activation-induced T-cell apoptosis, a phenomenon mediated by Fas/FasL interaction [17], is known to be inhibited in vitro by glucocorticoids through the downregulation of FasL expression in T cells [18,19]. This effect is controlled by the binding of ligand-bound glucocorticoid receptor to a negative glucocorticoid regulatory element within the fasL promoter [20,21]. This site overlaps with a NFkBbinding site, establishing a competition between ligand-bound glucocorticoid receptor and NFkB for the regulation of FasL expression [21].…”
Section: Resultsmentioning
confidence: 99%